2021
DOI: 10.1111/1440-1681.13587
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen sulphide attenuates neuronal apoptosis of substantia nigra by re‐establishing autophagic flux via promoting leptin signalling in a 6‐hydroxydopamine rat model of Parkinson's disease

Abstract: Previous studies reveal that hydrogen sulphide (H 2 S) exerts neuroprotection against neurotoxin-induced Parkinson's disease (PD), but the underlying mechanism remains elusive. The present study was aimed to investigate whether H 2 S inhibits neuronal apoptosis of substantia nigra with the involvement of autophagy via promoting leptin signalling in 6-hydroxydopamine (6-OHDA)-induced PD rats. In this study, neuronal apoptosis was analysed by TUNEL staining, the activity of caspase-3 was measured by Caspase-3 fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 77 publications
0
6
0
Order By: Relevance
“…Although several reports have demonstrated the involvement of MA in hydrogen sulfide-mediated neuroprotection, the effects of hydrogen sulfide on MA are also controversial [ 35 , 36 ]. Several studies have revealed that hydrogen sulfide exerts neuroprotective effects via the activation of MA [ 37 , 38 ], while MA inhibition contributes to the hydrogen sulfide-mediated neuroprotection [ 39 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although several reports have demonstrated the involvement of MA in hydrogen sulfide-mediated neuroprotection, the effects of hydrogen sulfide on MA are also controversial [ 35 , 36 ]. Several studies have revealed that hydrogen sulfide exerts neuroprotective effects via the activation of MA [ 37 , 38 ], while MA inhibition contributes to the hydrogen sulfide-mediated neuroprotection [ 39 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Experimental data connect metabolic deterioration and Parkinson’s disease (PD) with a dysregulation of central and peripheral neuroinflammatory networks mediated by several adipokines, particularly by leptin. Leptin had protective effects in an experimental model of PD, generated by a mitochondrial neurotoxin [ 114 ], and compounds that increase leptin signaling in a 6-hydroxydopamine rat model of PD attenuate neuronal apoptosis of substantia nigra [ 115 ].…”
Section: Functionality Of Leptin and Its Involvement In Pathologymentioning
confidence: 99%
“…On the other hand, the exogenous application of H 2 S promoted the increase in endogenous H 2 S and inhibited the movement disorder by reversing the depletion of tyrosine–hydroxylase-positive neurons in the SN. This protective effect may be mediated by promoting leptin signaling and increasing malondialdehyde levels in the striatum [ 110 , 111 ]. NaHS application could also protect SH-SY5Y cells against 1-methyl-4-phenylpyridinium ion (MPP + )-induced mitochondrial transmembrane potential loss, oxidative stress and cell apoptotic in the PD cell model [ 109 ].…”
Section: Involvement Of H 2 S In Neurological Dise...mentioning
confidence: 99%